2020
DOI: 10.1021/acsami.0c08033
|View full text |Cite
|
Sign up to set email alerts
|

Light-Triggered Trafficking to the Cell Nucleus of a Cationic Polyamidoamine Functionalized with Ruthenium Complexes

Abstract: Strategies for endosomal escape and access to the cell nucleus are highly sought for nanocarriers to deliver their load efficiently following endocytosis. In this work, we have studied the uptake and intracellular trafficking of a polycationic polyamidoamine (PAA) endowed with a luminescent Ru complex, Ru–PhenAN, that shows unique trafficking to the cell nucleus. Live cell imaging confirmed the capacity of this polymer to access the nucleus, excluding artifacts due to cell fixation, and clarified that the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Apoptotic cell death mechanism by the AO/EB staining assay of RuG0 , RuG1 , and RuG2 in A549, MDA MB 231, and HepG2 cells is shown in Figures , S16, and S17, respectively. As illustrated in the fluorescence microscopy images of Ru­(II) coordination entity-treated cells, the AO/EB staining clearly indicates that the coordination entities have induced apoptosis in the respective cell lines, as evident from the MTT assay. The AO/EB fluorescence microscopy images of HepG2 cell lines have shown higher apoptosis with the prepared coordination entities.…”
Section: Resultsmentioning
confidence: 83%
“…Apoptotic cell death mechanism by the AO/EB staining assay of RuG0 , RuG1 , and RuG2 in A549, MDA MB 231, and HepG2 cells is shown in Figures , S16, and S17, respectively. As illustrated in the fluorescence microscopy images of Ru­(II) coordination entity-treated cells, the AO/EB staining clearly indicates that the coordination entities have induced apoptosis in the respective cell lines, as evident from the MTT assay. The AO/EB fluorescence microscopy images of HepG2 cell lines have shown higher apoptosis with the prepared coordination entities.…”
Section: Resultsmentioning
confidence: 83%
“…Such nuclear stains are cationic in nature and highly aminated, which promotes electrostatic as well as hydrogen bonding interactions with the phosphate backbone of DNA . Similarly, previous studies have demonstrated that cationic nanoparticles preferentially target the nucleus. , To achieve this with aC′ dots, we condensed (3-(2-aminoethylamino)­propyl)­trimethoxysilane (AEAPTMS) onto the surface of DEAC-aC′ dots via PPSMI. Unreacted AEAPTMS was removed using GPC.…”
Section: Results and Discussionmentioning
confidence: 96%
“…43 Similarly, previous studies have demonstrated that cationic nanoparticles preferentially target the nucleus. 44,45 To achieve this with aC′ dots, we condensed (3-(2-aminoethylamino)propyl)trimethoxysilane (AEAPTMS) onto the surface of DEAC-aC′ dots via PPSMI. Unreacted AEAPTMS was removed using GPC.…”
Section: Three-color Labeling Of Actin and Tubulin Network As Well As...mentioning
confidence: 99%
“…Compared to the monomeric complex, the polymer exhibits similar subcellular distribution but remarkably lower (photo)cytotoxicity. Salvati, Maggioni, and co-workers have utilized a cationic PAMAM as the backbone for attaching ruthenium(II) complexes for PDT applications. , The resultant metallopolymer ( 149 ) shows more efficient cellular uptake in live HeLa cells compared to its zwitterionic counterpart 148b . It enters cells via an active uptake mechanism and undergoes trafficking along the endosomal/lysosomal compartments.…”
Section: Luminescent Transition Metal Conjugates For Bioimagingmentioning
confidence: 99%